Review: Single-molecule magnets based on pyridine alcohol ligands. Issue 21 (1st November 2016) - Bao, Dong-Xu; Xiang, Shuo; Wang, Jin; Li, Yun-Chun; Zhao, Xiao-Qing
Abstract: Single-molecule magnets (SMMs) have attracted attention due to their potential applications in quantum computation and information storage, and many SMMs have been reported in the past two decades. In this review, we summarize the structures and the magnetic exchange interactions of pyridine alcohol-based SMMs to give a possible relationship between structure and magnetic property, providing information to generate new molecule-based magnetic materials. According to the correlated metal centers, these SMMs are separated into three segments to discuss. Abstract :